Persistence of Post- COVID-19 Symptoms in Patients Attending Maitiga Preventive Medicine Center in Tripoli, Libya - Alshawish, Abdulrauf; Abubaker Elmaryul; Aboujela Allafi; Halima Buni (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Post-acute sequelae of COVID-19 is being diagnosed in patients who developed severe acute COVID-19, but occasionally also in patients who experienced mild or asymptomatic disease. The purpose of this study was to describe the presenting post-COVID-19 characteristics, persistence symptoms and risk factors of COVID-19 patients admitted to and/or visited Maitiga preventive medicine hospital in Tripoli-Libya during the period from November 2020 to November 2021. Methods. A cross sectional study was conducted, and included 935 patients had a confirmed diagnosis of COVID-19 by real time PCR, and aged 14 to 100 years. Data were collected manually from Maitiga Preventive Medicine Center records between 17th of November 2020 to 30th November 2021 included both inpatient and outpatient departments. Data were extracted by excel and further analyzed using SPSS. Results. The most frequently reported persistence post-COVID-19 symptoms were cough (26.3%); fatigue (24.3%) and dyspnea (24%). The most common prevalent comorbidities were diabetes mellitus (25.9%) followed by hypertension (11.9%) then cardiac diseases (4.2%). Conclusion. Diabetic patients were most frequent to be affected by COVID19 infection than other patients with chronic illness. Post COVID-19 persistence respiratory symptoms including cough and dyspnea are common to suffer by COVID-19 infected patients followed by fatigue. Cite this article: Alshawish A, Elmaryul A, Allafi A, Buni H. Persistence of Post- COVID-19 Symptoms in Patients Attending Maitiga Preventive Medicine Center in Tripoli, Libya. Alq J Med App Sci. 2022;5(2):488-492. https://doi.org/10.5281/zenodo.7156702